What Kapitan Tiago served and Padre Damaso ate : studies on Jose Rizal, his world, and his works - Torres, Jose Victor Z. (Quezon City : Ateneo de Manila University Press, 2021)
Who was Jose Rizal? While most Filipinos know him to be our national hero, many will find that there is a superficiality to their knowledge of the Filipino patriot. In this collection of essays, historian Jose Victor Z. Torres invites us to engage in an in-depth re-examination of how we see Rizal. Addressing the sociohistorical context of Rizal$1 (Bs nineteenth-century world, his novels, and his ambitions, Torres offers a thought-provoking perspective on Rizal. By stripping away the title of pambansang bayani and delving into a deeper, more personal understanding of who he was through this work, we can reconfigure our perception of Rizal to gain a richer appreciation of his life and legacy. Beyond looking at Rizal as a hero, we might want to discover who Rizal was at the end of the day$1 (Ba human being.s
Acknowledgements -- Introduction -- What Kapitan Tiago Served and Padre Damaso ate -- Telegrafo, Electricidad, y Punible Delito -- Annotating Colonial Histories -- A la Juvented de Filibusteros -- Bibliography.
Includes bibliographical references.
Keywords: RIZAL, JOSE 1861-1896 -- STUDY AND TEACHING; RIZAL, JOSE 1861-1896 -- LITERARY COLLECTIONS